The Effect of the Cooperative Integrated Reading and Composition (CIRC) Model on Reading Literacy Skills of Grade V Elementary School Students - Lestari, Eva Endah; Fajrin, Nilamsari Damayanti (Literasi Nusantara, 2025)
The purpose of this study was to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) model on the Reading Literacy Ability of Grade V Students of SDN Tanah Kalikedinding II Surabaya. This study used a quantitative method of quasi-experimental type with a Pretest-Postest Nonequivalent Control Group Design. The population of this study was grade V students of SDN Tanah Kalikedinding II Surabaya. The research sample was 60 students with the Purposive Sampling technique. Data collection used written tests and observation sheets for the implementation of the learning model. The data analysis technique used was the Independent Samples T-Test. The results of the study showed that from the independent sample t-test, Sig. (2-tailed) was obtained, namely 0.022 <0.05, then H0 was rejected and Ha was accepted. This means that there is a significant influence in the application of the Cooperative Integrated Reading snd Composition (CIRC) learning model on the reading literacy ability of grade V students of SDN Tanah Kalikedinding II Surabaya.